Integrated resource strategic planning and power demand-side management - Hu, Zhaoguang (Power Systems,, 2013)
Integrated Resource Strategic Planning and Power Demand-Side Management elaborates two important methods - Integrated Resource Strategic Planning (IRSP) and Demand Side Management (DSM) - in terms of methodology modeling, case studies and lessons learned. This book introduces a prospective and realistic theory of the IRSP method and includes typical best practices of DSM for energy conservation and emission reduction in different countries. It can help energy providers and governmental decision-makers formulate policies and make plans for energy conservation and emission reduction, and can help power consumers reduce costs and participate in DSM projects. Zhaoguang Hu is the vice president and chief energy specialist at the State Grid Energy Research Institute, and the head of the Power Supply and Demand Research Laboratory in China.